Extraction Of Secondary Metabolite In Tetraselmis Suecica Using Different Solvent Polarity - Din, Muhammad Alif Faiz Mohd (Universiti Sains Malaysia, 2020)
Recently, there has been much interest in secondary metabolites extracted from natural sources including microalgae for the food industry as well as pharmaceutical, cosmetic, and nutraceutical sectors. These interests have been increasing among researchers nowadays. Therefore, the present investigation was undertaken to analyse the secondary metabolite from Tetraselmis suecica which is a marine microalga. Briefly, T. suecica was cultured in normal conditions in the F/2 medium.